Pengaruh Kualitas Pelayanan Akademik terhadap Kepuasan Mahasiswa pada Sekolah Tinggi Ilmu Ekonomi Prabumulih - Susianti Susianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Evaluation of service quality at Prabumulih College of Economics is needed to find out what is actually expected and perceived by students with what has been offered. This study aims to determine the effect of academic service quality on student satisfaction at the Prabumulih College of Economics. The method used in this study is a survey method. The data collected consists of primary data and secondary data. Primary data obtained through the interview method that is equipped with a questionnaire that has been prepared. Secondary data were obtained from related companies, as well as several library sources in the form of journals and books relating to this research. And the method used in this research is survey method. The data collected consists of primary data and secondary data. Primary data obtained through the interview method that is equipped with a questionnaire that has been prepared. In this study, what will be analyzed is the effect of service quality consisting of 1) tangible (direct evidence) including physical facilities, equipment, employees, and communication facilities; 2) reliability, which is the ability to provide the promised service immediately, accurately and satisfactorily; 3) responsiveness (responsiveness), namely the desire of staff to help customers and provide services responsively; 4) assurance, including knowledge, competence, courtesy, and trustworthiness of staff, free from danger, risk or doubt; and 5) empathy (empathy), including ease in establishing relationships, good communication, personal attention, and understanding of the individual needs of customers. The results showed that physical evidence, reliability, responsiveness, assurance, concern and student satisfaction had a positive and significant effect on student satisfaction. Keywords: Quality of Service, the Satisfaction of College Students